Impact of child emotional and behavioural difficulties on educational outcomes of primary school children in Ethiopia: a population-based cohort study - Habtamu Mekonnen; Girmay Medhin; Mark Tomlinson; Atalay Alem; Martin Prince; Charlotte Hanlon (BMC, 2020)
Abstract Background The relationship between child emotional and behavioural difficulties (EBD) and educational outcomes has not been investigated in prospective, community studies from low-income countries. Methods The association between child EBD symptoms and educational outcomes was examined in an ongoing cohort of 2090 mother-child dyads. Child EBD was measured when the mean age of children was 6.5 years, SD 0.04 (T0) and 8.4, SD 0.5 years (T1) using the Strength and Difficulties Questionnaire (SDQ). Educational outcomes were obtained from maternal report (drop-out) at T1 and from school records at when the mean age of the children was 9.3 (SD 0.5) years (T2). Result After adjusting for potential confounders, child EBD symptoms at T1 were associated significantly with school absenteeism at T2: SDQ total score: Risk Ratio (RR) 1.01; 95% confidence interval (CI) 1.01, 1.02; SDQ high score (≥ 14) RR 1.36; 95% CI 1.24, 1.48; emotional subscale RR 1.03; 95% CI 1.01, 1.04; hyperactivity subscale RR 1.03; 95% CI 1.02, 1.04 and peer problems subscale (RR 1.02; 95% CI 1.00, 1.04). High SDQ (β = − 2.89; 95% CI − 5.73, − 0.06) and the conduct problems sub-scale (β = − 0.57; 95% CI − 1.02, − 0.12) had a significant negative association with academic achievement. There was no significant association between child EBD and school drop-out. Conclusion Prospective associations were found between child EBD symptoms and increased school absenteeism and lower academic achievement, suggesting the need for child mental health to be considered in interventions targeting improvement of school attendance and academic achievement in low-income countries.